Synthesis and characterization of green porous carbons with large surface area by two step chemical activation with KOH - Nasri, Noor Shawal (Penerbit UTM Press, 2014)
Porous carbons were synthesized from coconut shell using chemical activation by potassium hydroxide (KOH). N2 adsorption isotherm analysis for BET surface area and pore volume of the synthesized porous carbon were carried out. The Langmuir surface area, BET surface area and pore volume are 1646 m2/g, 1353 m2/g and 0.6 cm3/g, respectively. From the FTIR analysis, hydroxyls, alkenes, carbonyls and aromatics functional groups were identified. The proximate and ultimate analysis shows high percentage of carbon and less ash content which indicates a good precursor material for porous carbon. The carbonization temperature and time were also varied to observe their effect on the yield of char, with carbonization at 700°C for 2 h having highest yield of 32%.